2D sound source position estimation using microphone arrays and its application to a VR-based bird song analysis system. (18th April 2019) - Gabriel, D.; Kojima, R.; Hoshiba, K.; Itoyama, K.; Nishida, K.; Nakadai, K.
ABSTRACT: This paper addresses the problem of 2D sound source localization using multiple microphone arrays in an outdoor environment. Two main issues exist in such localization. Since the localization performance depends on a variety of parameters, the lack of knowledge about how to design the system is one of those issues. A thorough analysis in respect to the accuracy of the localization results with different simulation conditions has been performed. Obtained characteristics lead to a discussion on limitations and applicability of the system. The distinction between multiple simultaneous sound sources is another problem. This is directly related to the appearance of outliers in the localization process. To solve this issue, an outlier removal method is proposed, which takes the properties of the observed sounds into consideration. In this paper a VR-based visualization method of the obtained results is also introduced. As the application scenario, we selected bird song analysis, which provides a challenging environment in terms of constantly changing signal-to-noise ratio and relative sensor-to-target position. A prototype system has been established using the proposed method. Several simulation results have been presented followed by a discussion on the issues. This leads to establishing system design guidelines that ensure a predictable performance. GRAPHICAL ABSTRACT: